2012
DOI: 10.1007/s00213-012-2812-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated treatment with topiramate on voluntary alcohol intake and beta-endorphin plasma level in Warsaw alcohol high-preferring rats

Abstract: RationalePharmacological treatment currently used for alcohol dependence is not sufficient for the all patients, and there is a crucial need to find more effective treatments. Recent studies indicate that topiramate is likely the most promising new medication for alcohol dependence. The rationale for topiramate as treatment for alcohol addiction is based on its multifaceted neurochemical activity that targets multiple neural pathways.ObjectivesThis study aims to assess the effect of repeated treatment with top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
(49 reference statements)
1
14
0
1
Order By: Relevance
“…Future studies should address the issues that most of the drugs only reduced drinking when the drug was onboard, not many studies have examined anticonvulsants in relapse models, and some of the studies demonstrated tolerance to the effects of the drugs. Some of the anticonvulsants only reduced consumption in alcohol-preferring(9, 10), high-drinking(5), or alcohol-dependent rodents(17). This suggests that genetics and/or chronic alcohol induced neuroadaptations may affect the efficacy of these drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should address the issues that most of the drugs only reduced drinking when the drug was onboard, not many studies have examined anticonvulsants in relapse models, and some of the studies demonstrated tolerance to the effects of the drugs. Some of the anticonvulsants only reduced consumption in alcohol-preferring(9, 10), high-drinking(5), or alcohol-dependent rodents(17). This suggests that genetics and/or chronic alcohol induced neuroadaptations may affect the efficacy of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Topiramate also reduced stress-induced escalation of alcohol consumption and preference in C57BL/6J mice(8). In Warsaw high preferring (WHP) and P rats, repeated treatment (5 - 14 days) with topiramate significantly diminished voluntary consumption and preference for 10% alcohol in a standard two-bottle choice paradigm(9, 10). Tolerance to repeated administration was not observed in these studies, as topiramate was equally effective at reducing drinking throughout the treatment period.…”
Section: Topiramatementioning
confidence: 99%
“…Topiramate is often used, off-label, as a treatment for alcoholism, and inhibits glutamate release and blocks L-alpha-amino-3-hydroxy-5-methyl-isoxazole-4-propionic acid ionotropic (AMPAR)/ kainate receptors (KAR) as part of a complex pharmacological profile. In rodents, topiramate promotes alcohol intoxication and reduces alcohol drinking and withdrawal, but does not disrupt alcohol place preference (Breslin et al 2010; Cagetti et al 2004; Chen and Holmes 2009; Farook et al 2007; Gremel et al 2006; Hargreaves and McGregor 2007; Knapp et al 2007; Lynch et al 2011; Nguyen et al 2007; Zalewska-Kaszubska et al 2013). Topiramate also reduces craving, withdrawal and drinking in alcoholics (Baltieri et al 2008; Florez et al 2008; Johnson et al 2004; Johnson et al 2003a; Johnson et al 2007; Komanduri 2003; Krupitsky et al 2007b; Miranda et al 2008; Paparrigopoulos et al 2011; Rubio et al 2004; Rustembegovic et al 2002).…”
Section: Glutamate Signaling As a Target For New Alcoholism Treatmentsmentioning
confidence: 99%
“…Another PPAR agonist, clofibrate, prevents the acquisition of nicotine self-administration in naïve rats and monkeys and decreases nicotine self-administration in nicotine-dependent rats and monkeys, suggesting that the PPAR agonist might be viable options for treating the neuroimmune pathologies in alcoholism and other forms of addiction. The pharmacologic blockade of neuroimmune activation reduces alcohol reward and decreases consumption using many types of anti-inflammatory drugs like minocycline, doxycycline, topiramate, anakinra, indomethacin, and CAPE (Agarwal, 2001; Pascual et al, 2007; Breslin et al, 2010; Wu et al, 2011; McIver et al, 2012; Blednov et al, 2013; Zalewska-Kaszubska et al, 2013). Taken together, these findings have built substantial evidence for neuroimmune modulation of acute and chronic alcohol consumption and offer unique unexplored targets for therapeutic intervention.…”
Section: Molecular Mechanisms Underlying Acute and Chronic Alcoholismmentioning
confidence: 99%